Secondhand tobacco smoke exposure in homes and vehicles in youth: disparities among racial, and sexual and gender minorities - Rajesh Talluri; Sahil S. Shete; Surendra S. Shastri; Sanjay Shete; Sanjay Shete; Sanjay Shete (Frontiers in Public Health, 2024)
BackgroundSecondhand smoke exposure (SHSe) among youth is a serious public health concern, leading to an increased risk of conditions such as asthma and respiratory infections. However, there is little research on SHSe among vulnerable populations, such as racial and sexual minorities. Understanding the factors associated with youth SHSe in homes and vehicles is crucial to developing better protective policies.MethodsThis study utilized 2020 data from the National Youth Tobacco Survey, a representative sample of middle- and high-school students in the US. The primary outcomes were youth SHSe at home and while riding in a vehicle. Multinomial regression models were used to assess factors associated with SHSe.ResultsThe data included 9,912 students enrolled in grades 6 through 12 in the United States who reported never using any form of tobacco. Non-Hispanic Black students living with someone who does not use any form of tobacco products were significantly more likely to experience moderate [OR = 2.1 (1.1–3.9), p = 0.03] and severe [OR = 5.1 (2.2–11.7), p < 0.001] secondhand smoke exposure (SHSe) in homes compared to their non-Hispanic White counterparts. Heterosexual female students had lower odds of reporting moderate SHSe in the home compared to heterosexual males [OR = 0.7 (0.6–0.99), p = 0.02], whereas bisexual females had two-fold increased odds of severe SHSe in homes [OR = 2.0 (1.2–3.4), p = 0.01].ConclusionSignificant efforts are needed to develop targeted interventions to reduce SHSe in homes and vehicles, particularly in these vulnerable populations.